Hemolysin Production as a Virulence Marker in Symptomatic and Asymptomatic Urinary Tract Infections Caused by Escherichia coli - Hughes, Colin (1983)
Potential virulence, as defined by combined levels of adhesion to urinary epithelial cells, serum resistance, and mouse toxicity, was assessed for Escherichia coli strains causing symptomatic and asymptomatic urinary tract infections in relation to the carriage of hemolysin and other suspected virulence determinants. Hemolysin production (Hly), associated with certain O (O4, O6, O18, and O75), K (5), and hemagglutination (VI and VII) antigenic types but not colicin V production (Cva), was evident in 83 and 60% of isolates in groups possessing high potential virulence and in only 11 and 6% of those with low virulence. Strains of particular O-types were not more virulent per se, but among the serotypes, specific combinations of virulence factors appeared decisive, e.g., O18 HAVI B/D/G Hly(+) K5(+/−) and O18 HAIII/IVB/V Hly(−) Cva(+/−) K1(+/−) strains were, respectively, of high and low potential virulence. Isolates with high potential virulence were found to a similar extent in symptomatic and asymptomatic infections.